An experimental study of word learning in minimally verbal children and adolescents with autism spectrum disorder. (March 2019) - Joseph, Robert M; Skwerer, Daniela Plesa; Eggleston, Brady; Meyer, Steven R; Tager-Flusberg, Helen
Background and aims: When children hear a novel word, they tend to associate it with a novel rather than a familiar object. The ability to map a novel word to its corresponding referent is thought to depend, at least in part, on language-learning strategies, such as mutual exclusivity and lexical contrast. Although the importance of word learning strategies has been broadly investigated in typically developing children as well as younger children with autism spectrum disorder, who are usually language delayed, there is a paucity of research on such strategies and their role in language learning in school-age children and adolescents with autism spectrum disorder who have failed to develop fluent speech. In this study, we examined the ability of minimally verbal children and adolescents with autism spectrum disorder to learn and retain novel words in an experimental task, as well as the cognitive, language, and social correlates of these abilities. We were primarily interested in the characteristics that differentiated between three subgroups of participants: those unable to use word learning strategies, particularly mutual exclusivity, to learn novel words; those able to learn novel words over several exposure trials but not able retain them; and those able to retain the words they learned. Methods: Participants were 29 minimally verbal individuals with autism spectrum disorder from 5 to 17 years of age. Participants completed a computerized touchscreen novel-word-learning procedure followed by assessments of immediate retention and of delayed retention, two hours later. Participants were grouped according to whether they passed/failed at least 7 of 8 (binomial p < .035) novel word learning trials and 7 of 8 immediate or delayed retention trials, and were compared on measures of nonverbal IQ, receptive and expressive vocabulary, phonological processing, joint attention and symptom severity. Results: Of 29 participants, 14 failed both learning and immediate retention, 8 passed learning but failed immediate retention, and 7 passed both learning and immediate retention. Group performance was highly similar for delayed retention. Language level, particularly expressive vocabulary, differentiated between participants who did and did not succeed in retention, even while controlling for differences in nonverbal IQ. Conclusions: The ability of minimally verbal school-age children and adolescents with autism spectrum disorder to identify the referents of novel words was associated with nonverbal cognitive abilities. Retention of words was associated with concurrent expressive language abilities. Implications: Our findings of associations between the retention of novel words acquired in a lab-based experimental task and concurrent language ability warrants further investigation with larger samples and longitudinal research designs, which may support the incorporation of contrastive word learning strategies into language learning interventions for severely language-impaired individuals with autism spectrum disorder.